A comparative study of acute heat tolerance and meat quality in three chicken breeds. (13th April 2022) - Liang, Hsiao‐Mei; Chang, Ti‐Chun; Lin, Der‐Yuh; Yang, Kuo‐Tai; Cheng, Fu‐Yuan
Abstract: In order to breed a strain that has heat tolerance and meat productivity, the commercial red‐feathered Taiwan native chickens were male (F group), and heat stress resistant strain Taiwan native chickens (Taishu‐9, bred by the Taiwan Livestock Research Institute) were female (TR9 group) to hybridize to generate offspring (F9 group). Three breeds of birds (male) were conducted to compare acute heat stress and meat quality. At 12 weeks of age, TR9 group showed the significantly lowest activity of plasma creatine kinase upon acute heat stress which indicated heat stress resistant in TR9 group as expected. In addition, only limited thermoregulation was obtained in F9 group, while F group exhibited almost no acute heat stress tolerance ability. After slaughtered at 16 weeks of age, the F group revealed poor meat quality in breast meat as pale, soft, and exudative (PSE)‐like muscle samples according to CIE L* and pH value. The F9 group was an offspring of TR9 group with heat tolerance, but it only demonstrated limitation of heat resistance. However, the improve meat quality was obtained in F9 group compared to F group, and that may be contributed from better anti‐stress as like as TR9 group during slaughtering process.